EXAMINING INDONESIA'S ISLAMIC COMMERCIAL BANKS HEALTH STATUS USING THE RBBR METHOD - Puspita Sari, Anggi; Sukardi, Budi (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
The scientific importance of Indonesia's Islamic banks' state is the focus of this study using a strategy based on the Risk-based Bank Rating technique. This quantitative descriptive research analyzes the health of Indonesia's Islamic commercial banks, namely Bank Syariah Indonesia and Bank Muamalat Indonesia, for the years 2019 to 2022, focusing on the degree of bank health as measured by the RBBR approach. The study's data analysis leads to the conclusion that Bank Syariah Indonesia's overall condition is represented by a Composite Rank 2 (PK-2) of 85% in 2019, meaning that it is deemed